The Role of Green Global Human Resource Management in Achieving Sustainable Manufacturing - Reonold Dwi Aditya; Riski Febriani (Jurnal Manajemen Bisnis Era Digital, 2025)
Companies that focus on the manufacturing industry are one of the sectors that have a major impact on the environment. The existence of intensive production processes and the use of large amounts of natural resources have significant environmental and social impacts, both directly and indirectly. The application of green global human resources in the manufacturing industry has a role in shaping corporate culture and guiding policies that support the transition to sustainable companies. Research on the topic of GHRM has been rampant in recent years, but this topic has been widely discussed since 2021. The relevance of the discussion of GHRM to support manufacturing with sustainability can be supported by practices in companies, the application of a corporate culture that is aware of the interests of sustainability